Vitamin D and Its Role in Modulating Immune System: A Narrative Literature Review - Rizkia, Chaula Putri (HM Publisher, 2023)
Vitamin D is recognized for its pivotal role in maintaining calcium-phosphorus homeostasis and regulating bone metabolism. The beneficial effects of vitamin D on the protective function of the immune system are seen in the innate immune system. It increases the production of defensin β2 and cathelicidin by macrophages, monocytes, and keratinocytes in response to infection. Cathelicidin is produced by neutrophils, macrophages, and cells lining epithelial surfaces such as skin, respiratory, and digestive tracts. Recent research showed that vitamin D exerts potent immunomodulatory effects by modulating the innate and adaptive immune systems. This led to the recognition of various disease conditions associated with vitamin D deficiency. This narrative review aimed to describe the molecular mechanisms for the vitamin D immunomodulatory effect.